1992
DOI: 10.1177/00220345920710090401
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of the Gap Region in the 23S Ribosomal RNA from Actinobacillus actinomycetemcomitans

Abstract: Actinobacillus actinomycetemcomitans is a Gram-negative coccobacillus which can cause certain severe extra-oral infections as well as forms of human periodontal disease such as localized juvenile periodontitis. In contrast to many prokaryotic and eukaryotic species which exhibit an intact 23S ribosomal RNA (rRNA) molecule, examination of six A. actinomycetemcomitans strains--including three serogroup representative strains and two strains from non-human primates--revealed that this micro-organism does not prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The 1170 position is also at a position homologous to an expansion segment in eucaryotes (41). The five internal spacers reported by Van Camp et al (60) were also located in this helix, as were transcribed spacers of Salmonella (3), Yersinia (52), Actinobacillus (20), Leptospira (52), and Chlamydomonas chloroplasts (59) U-1859-C-1883 the true campylobacters, including C. coli, appear to belong to a previously undefined phylogenetic branch, on the basis of a signature sequence analysis and comparison of sequence data with partial sequences of representatives of 8 of the 10 major phylogenetic branches of the (eu)bacteria. Lau et al (30) subsequently suggested that while there is some evidence of affinity between an expanded division containing the purple photosynthetic bacteria and their relatives and the Campylobacter cluster, the Campylobacter cluster is not specifically positioned in either the alpha, beta, or gamma subdivision of the group.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The 1170 position is also at a position homologous to an expansion segment in eucaryotes (41). The five internal spacers reported by Van Camp et al (60) were also located in this helix, as were transcribed spacers of Salmonella (3), Yersinia (52), Actinobacillus (20), Leptospira (52), and Chlamydomonas chloroplasts (59) U-1859-C-1883 the true campylobacters, including C. coli, appear to belong to a previously undefined phylogenetic branch, on the basis of a signature sequence analysis and comparison of sequence data with partial sequences of representatives of 8 of the 10 major phylogenetic branches of the (eu)bacteria. Lau et al (30) subsequently suggested that while there is some evidence of affinity between an expanded division containing the purple photosynthetic bacteria and their relatives and the Campylobacter cluster, the Campylobacter cluster is not specifically positioned in either the alpha, beta, or gamma subdivision of the group.…”
Section: Discussionmentioning
confidence: 68%
“…2 and 3A). Similar sequence blocks have been shown to be present at this position in the 23S rRNA genes from a variety of bacteria (3,20,44,47,52,60) and chloroplasts (59), and these extra sequence blocks in the 23S rRNA genes have been termed intervening sequences (3) or transcribed spacers (60).…”
Section: Resultsmentioning
confidence: 85%
“…S1 in the supplemental material), at least so far as 23S rRNA sequences are available to date, but it contains two intervening elements (Fig. 1A) similar to ones found in the rRNA genes of diverse species (e.g., see references [30][31][32], including other giant sulfur bacteria (33). In orange Guaymas Beggiatoa, a putative group I catalytic intron is found at E. coli position 1917, in the loop of predicted helix 69, and a putative LAGLIDADG homing endonuclease at E. coli position 1931, in a predicted unstructured region between helices 69 and 71 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Eubacterial 23S rRNA genes (rrl) have been observed that carry small insertions of about 90-112 bases that are removed by cleavage but not religated (8)(9)(10). These IVSs have been found in only some strains within species in a few genera, implying that the IVS may be maintained by lateral transfer between strains but is not necessarily required for host survival.…”
mentioning
confidence: 99%